Approximation to the Use of the Color Vowel ®Approach to Foster 4th Graders’ Decoding Skills for Vowels /i:/, /u/, /eɪ/, and /aʊ/ - Matus, Isabel; Inostroza Araos, María-Jesús (Colombian Applied Linguistics Journal, 2024)
This action research study focuses on an approximation to the use of the Color Vowel ® approach to enhance learners’ decoding skills. Teaching young learners to read in a second language, identify spellings and sounds that may differ from their first language, and develop phonological awareness poses a significant and challenging task that demands thoughtful consideration. This study was conducted in a subsidized school in Talcahuano, Chile. Data was collected from a group of 4th-grade students using a checklist as a pre- and post-intervention test to analyze their decoding skills, along with a Likert scale and focus group to identify their perceptions on the use of the strategy. The results showed that the Color Vowel ® approach improved learners’ decoding skills, particularly in developing and accurately producing vowel sounds among 4th graders. Additionally, the students expressed positive perceptions of this approach, highlighting the importance of learning English pronunciation for their daily and future lives. These findings could shed light on the importance of explicit phonological awareness instruction, as well as the significance of considering young learners’ voices about the implications that language learning has on their lives.